Desain Didaktis Konteks Fabel Berbasis Pemahaman Matematis Siswa pada Materi Aljabar - Surya Amami Pramuditya; Muchamad Subali Noto; Via Dwi Handayani (Universitas Hamzanwadi, 2021)
This research is motivated by the importance of students 'mathematical understanding, but the fact is that students' mathematical understanding is still low in working on algebraic form questions. This problem brings out a learning obstacle, where students cannot interpret the algebraic form elements and cannot operate the algebraic form. This study aimed to design a didactic design phase using fables based on students' mathematical understanding. The research method is descriptive qualitative research. Design is Didactical Design Research (DDR) with 15 junior high school students as subjects. The data was collected using triangulation techniques, then analyzed descriptively. This study results in a didactic design in the form of a situation that can anticipate students' learning obstacles in algebraic form material and facilitate students' thinking process. Situations are created using exciting pictures and stories to motivate student learning. The results show that the situations that have been created make it easier for students to group similar and dissimilar terms and can operate the algebraic form easily and algorithmically. The students also can interpret the elements of the algebraic form along with addition and subtraction operations in the algebraic form based on the understanding of each student.